Dear development practitioner
1 online resource
Keywords: "In this book, influential development practitioners reflect on their careers by writing letters of advice to their younger selves. Sharing their successes and failures, the challenges and barriers they have encountered, and the changes and continuities within their work, these deeply personal accounts provide an invaluable window into the world of development practice. The authors come from nearly 20 countries. They have held a rich mix of jobs across a range of sectors and organisational types, bringing a long-term perspective to the sector's contemporary challenges. The distinguished list includes a Nobel prize winner, senior figures in government and international organisations, those working at the frontline of humanitarian aid and civil society organisations, and those who might not even have thought of themselves as 'development professionals', such as technologists and social entrepreneurs. Despite the differences, common themes emerge: the pursuit of meaningful change, the navigation of barriers, and the ongoing sense of hope. This book will inspire those about to embark on their professional careers and remind new entrants and current development practitioners alike how much there remains to be done"--